Evaluation of veteran community care outcomes after coronary artery bypass grafting: a retrospective pilot cohort - Jake L Cotton; Adom Netsanet; Alejandro Suarez-Pierre; Danielle Abbitt; Teresa S Jones; Jessica Y Rove; Edward L Jones (Journal of Cardiothoracic Surgery, 2024)
Abstract For Veterans who cannot be seen in a timely fashion or must travel long distances to be seen, the Veterans Health Administration (VHA) offers funded care in the community. The use of this program has rapidly increased; however, there have been no systematic evaluations of surgery specific metrics such as perioperative complications, mortality and timeliness of care. To evaluate this in cardiac surgery patients, we compared veterans undergoing coronary artery bypass grafting in the community to those remaining within the VHA. We identified 78 patients during calendar year 2018 meeting inclusion criteria. 41 underwent surgery in the community versus 37 in the VHA. There were no significant differences in baseline demographics including age, sex, race, ethnicity, comorbidities and surgical risk scores. With regard to perioperative outcomes, veterans who underwent surgery within the VHA had lower infection rates (17% vs. 0%, p = 0.008) and 30-day emergency department utilization (22% vs. 5%, p = 0.04). A longer median postoperative inpatient stay was also seen within the VHA (8 days vs. 6 days, p < 0.001). These findings suggest that the VHA may better serve Veterans and prevent adverse events after CABG, at the expense of prolonged hospitalization. More study is needed to validate the findings of this pilot study.